Endoscopic radiofrequency ablation for the treatment of severe gastric antral vascular ectasia in patients with cirrhosis. Issue 11 (November 2021) - Senzolo, Marco; Realdon, Stefano; Zanetto, Alberto; Simoncin, Beatrice; Schepis, Filippo; Caronna, Stefania; Saracco, Giorgio Maria; De Angelis, Claudio Giovanni; Debernardi Venon, Wilma
Abstract : Introduction: Gastric antral vascular ectasia is a significant cause of gastrointestinal bleeding in patients with cirrhosis. Aim: To assess safety/efficacy and cost/advantages of radiofrequency ablation for the treatment of gastric antral vascular ectasia in patients with cirrhosis. Materials and methods: Patients with cirrhosis and severe gastric antral vascular ectasia who underwent radiofrequency ablation were enrolled. Clinical data, gastric antral vascular ectasia grade, and gastric antral vascular ectasia-related hospitalizations were collected. Primary outcome was defined as the absence of transfusion over the 6 months after radiofrequency. An economic analysis was performed in the same period. Results: Forty patients (50% Child B) were enrolled (80% refractory to argon plasma coagulation). Gastric antral vascular ectasia eradication was obtained in all patients and 65% of these patients achieved primary outcome. After radiofrequency, mean number of red blood cells transfusions dropped (from 25 to 0.9, P < 0.0001), with a parallel increase in hemoglobin (from 8 to 10.5 g/dL, P < 0.0001). No major complication occurred and liver function remained stable in all patients. The cost-analysis demonstrated a profound reduction of health care cost (from [Euro sign] 536.084 to [Euro sign] 189.044 in the 6 months before vs. after radiofrequency, respectively). These results were confirmed in the subgroup analysis in patients refractory to argon plasma coagulation. Conclusions: Radiofrequency ablation is safe and effective for the treatment of gastric antral vascular ectasia in patients with cirrhosis, including those refractory to argon plasma coagulation. Although the cost of single radiofrequency ablation is relatively high, the cost-analysis demonstrated considerable saving. Abstract : Supplemental Digital Content is available in the text.